Asuhan Keperawatan pada Ny. D dengan Post Operasi Tumor Mammae Dextra di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Iin Nurlatipah; Ahmad Zakiudin; Sukirno Sukirno (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Mammary tumor is a condition where an abnormal mass or lump forms in the breast, caused by excessive and continuous cell reproduction. This condition often develops unnoticed and can be dangerous if not promptly treated. In 2018, the incidence rate of breast cancer in Indonesia was 136.2 per 100,000 people, making it one of the most common cancers in Southeast Asia, ranking 8th in the region. If untreated, mammary tumors have the potential to spread to other parts of the body, and in many cases, can be fatal for the patient. One of the common medical treatments for mammary tumors is surgery. This surgery aims to remove the tumor and prevent further spread. In this context, the role of nurses is critical, as according to Orem's theory, nurses have the responsibility to help improve the health status of patients, especially in situations where patients are unable to perform self-care. In such cases, nursing assistance is necessary to ensure that the patient can undergo proper post-operative care. This study aims to provide an overview of nursing care for patients with post-operative right mammary tumor in the Mawar 2 room at RSUD dr. Soeselo, Tegal Regency. The nursing care provided includes several important steps: patient assessment, nursing diagnosis, planning, implementation of care, and evaluation of the care outcomes. This research uses a descriptive case study design, offering an in-depth view of the nursing approach applied to patients after mammary tumor surgery. With this approach, the study aims to provide clearer insights into the role of nurses in supporting patient recovery and improving the quality of care in hospitals.